Penerapan Sanksi Administrasi Bagi UMKM (Usaha Mikro Kecil Menengah) yang Melakukan Pencemaran Lingkungan di Kota Medan - Sabrina Utami Ningrum; Marlina Elisabeth Pakpahan (CV Rewang Rencang, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in economic development and reducing unemployment in Indonesia, including in Medan City. This study analyzes the application of administrative sanctions against MSMEs that pollute the environment in Medan City. Four main inhibiting factors were found: inconsistent regulations, weak law enforcement, low environmental awareness, and limited expertise. A case study of pig farm waste pollution in Kwala Bekala shows the effectiveness of preventive and reparative administrative sanctions. The study uses a normative legal method with a descriptive-analytical approach. The legal basis used includes Law No. 32 of 2009, Regulation of the Minister of Environment No. 2 of 2013, and Medan City Regulation No. 1 of 2016.